Digital marketing for processed waste business at Arnetta Craft - Dinda Permatasari; Nuril Kusumawardhani; Sevenpri Candra; Sulistyo Heripracoyo (Universitas Muhammadiyah Magelang, 2022)
In today's digital era, business and the internet are an inseparable combination. Businesses that do not use the internet daily will find it difficult to survive. Especially due to the COVID-19 pandemic where all activities must turn online. These changes and challenges that occur rapidly not only affect large companies, but also local MSME actors. Arnetta Craft is a local Indonesian handicraft business that specializes in the manufacture of candle fragrances, natural soaps, fashion, and other similar handicrafts. To survive in the current situation, Arnetta Craft must maximize digital marketing. From all these activities resulted in the creation of a simple website that can increase the credibility of the business and reach a wider target customer